Paediatric cardiac surgery for a continent – The experience of the Walter Sisulu Paediatric Cardiac Centre for Africa - Kinsley, Robin Howard; Edwin, Frank; Colsen, Peter Richard; Mamorare, Hendrick; Martin, Greg; Brink, Johann (SA Heart Journal, 2017)
Very few African countries have the resources to provide optimum paediatric cardiac services to their largely indigent populations. In the current era, in countries with access to modern paediatric cardiac care, mortality for congenital heart disease occurs more often in adulthood than in childhood. This level of care is largely unavailable in Africa. The Walter Sisulu Paediatric Cardiac Centre for Africa was set up in 2003 as a public-private collaborative initiative to extend modern paediatric cardiac care to the continent. Three core functions form the basis of our operations: service delivery, training, and research. This communication reviews our experience with this effort over an eight-year period. We have performed 2 023 procedures on 1 738 patients including a large proportion of neonates and infants with an overall mortality of 7.1%. Our charity arm sponsored 21.5% of these patients. We have encountered problems peculiar to the African context which we discuss. We also describe innovative techniques in management of specific patient populations. Our training efforts yielded two qualified paediatric cardiac surgeons who now work at the centre and two additional surgeons are in training. We have participated in research leading to publication of papers in peer-reviewed journals. In spite of our achievements, we recognise the enormous challenges faced by the continent in terms of paediatric cardiac care. An attempt has been made to quantify the burden of congenital disease in Africa to guide planning and training. We offer recommendations on how to address some of these pressing health issues for children of the continent.